2022
DOI: 10.3390/cryst12070908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu(II) and Zn(II) Sorption onto Zeolite

Abstract: In this study, a batch sorption study approach was combined with an instrumental analytical approach of atomic absorption spectroscopy, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) for the sorption of copper and zinc ions from aqueous solution on zeolites. Both copper and zinc are biogenic elements; nevertheless, many industrial processes produce an excessive amount, which is why their efficient removal from water must be studied. Two types of zeolites, Zeolite Micro 20 (Z-M20) and Zeolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…When the adsorption capacity of commercial adsorbents is examined in table 5, it is seen that Amberlite R-120 resin [70] and graphene oxide [71] have considerably higher adsorption capacities than hemp biosorbent. It has been observed that activated carbon [72,73] and zeolites [74,75] have higher adsorption capacities than hemp biosorbents, depending on their type. These commercial adsorbents can perform well to remove heavy metals, but are often expensive and environmentally unsustainable [41].…”
Section: 3mentioning
confidence: 99%
“…When the adsorption capacity of commercial adsorbents is examined in table 5, it is seen that Amberlite R-120 resin [70] and graphene oxide [71] have considerably higher adsorption capacities than hemp biosorbent. It has been observed that activated carbon [72,73] and zeolites [74,75] have higher adsorption capacities than hemp biosorbents, depending on their type. These commercial adsorbents can perform well to remove heavy metals, but are often expensive and environmentally unsustainable [41].…”
Section: 3mentioning
confidence: 99%
“…Furthermore, the ease of performance and the possibility of multiple reuses, with no by-products, make the adsorption process an excellent choice for wastewater treatment [ 5 , 15 ]. In general, many materials, such as zeolite, clay minerals, activated carbon, silica, and magnetic particles, have been studied as adsorbents to remove metal ions from the aqueous phases [ 16 , 17 , 18 , 19 , 20 ]. In the last few years, a growing research interest has been focused on low-cost adsorbents as alternatives to manufactured adsorbents.…”
Section: Introductionmentioning
confidence: 99%